Strength and conditioning: biological principles and practical applications (Wiley-Blackwell, 2011)
This book provides the latest scientific and practical information in the field of strength and conditioning. The text is presented in four sections, the first of which covers the biological aspects of the subject, laying the foundation for a better understanding of the second on the biological responses to strength and conditioning programs. Section three deals with the most effective monitoring strategies for evaluating a training program and establishing guidelines for writing a successful strength and conditioning program. The final section examines the role of strength and conditioning as a rehabilitation tool and as applied to those with disabilities. This book is an invaluable textbook and reference both for academic programs and for the continuing education of sports professionals. •Integrates the latest research on physiological, anatomical and biomechanical aspects of strength and conditioning •Offers numerous practical examples of applications •Provides guidelines for writing and monitoring effective strength training programs (Klappentext)